Development of a Measure to Assess Healthcare Providers' Implementation of Patient‐Centered Care. (15th July 2014) - Sidani, Souraya; Collins, Laura; Harbman, Patti; MacMillan, Kathleen; Reeves, Scott; Hurlock‐Chorostecki, Christina; Donald, Faith; Staples, Patti; van Soeren, Mary
ABSTRACT Background Patient‐centered care (PCC) is a vaguely defined element of high‐quality care, which precludes its consistent and precise operationalization. A conceptualization of PCC was derived from the literature and guided the development of an instrument to assess implementation of PCC by healthcare providers. The items of the instrument capture specific activities that reflect three components of PCC: holistic, collaborative, and responsive care. This paper reports on the measure's content and construct validity and reliability. Methods Content validity was evaluated in a sample of 11 nurse practitioners who rated the relevance of each items' content in reflecting the respective component of PCC. The content validity index (CVI) was estimated. Construct validity and internal consistency reliability were examined in a survey of 149 nurse practitioners employed in acute care institutions, using factor analysis and the KR‐20 coefficient, respectively. Results The CVIs were 100% for the three subscales assessing the holistic, collaborative, and responsive care components of PCC. The items in each subscale loaded on one factor. The KR‐20 coefficients were .66, .70, and .42, respectively. Overall, the majority (>70%) of respondents indicated performance of the activities comprising the three components of PCC. Linking Evidence to Action The PCC measure demonstrated acceptable psychometric properties. The low variance in responses, which is anticipated for instruments assessing fidelity of intervention implementation, accounts for the low reliability coefficients. Additional testing of the measure's psychometric properties in different groups of healthcare providers is warranted. The measure can be used to monitor healthcare providers' implementation of PCC in their usual practice.